Distance still matters: Local bank closures and credit availability. (19th August 2020) - Kärnä, Anders; Manduchi, Agostino; Stephan, Andreas
Abstract: In recent years, commercial banks have substantially reduced the number of their branch offices. We address the question of whether or not the increased distance to lenders caused by branch office closures translates into a lower credit supply for small and medium sized enterprises (SMEs). We use a unique dataset based on 33, 000 loan contracts from a state‐owned Swedish bank designed to support credit‐constrained SMEs, and relate loan size and the interest rate to the number of nearby commercial bank offices. We use an IV strategy to account for potential endogeneity of the number of banks in a region. In line with previous studies, we find that interest rates increase with distance, while loan size decreases with distance. Thus, a larger number of local bank offices increases the local credit supply, and thereby reduces credit constraints of nearby SMEs.